Determinants of fluconazole resistance and echinocandin tolerance in C. parapsilosis isolates causing a large clonal candidemia outbreak among COVID-19 patients in a Brazilian ICU. Issue 1 (31st December 2022) - Daneshnia, Farnaz; de Almeida Júnior, João N.; Arastehfar, Amir; Lombardi, Lisa; Shor, Erika; Moreno, Lis; Verena Mendes, Ana; Goreth Barberino, Maria; Thomaz Yamamoto, Danilo; Butler, Geraldine; Perlin, David S.; Colombo, Arnaldo Lopes
ABSTRACT: Patients presenting with severe COVID-19 are predisposed to acquire secondary fungal infections such as COVID-19-associated candidemia (CAC), which are associated with poor clinical outcomes despite antifungal treatment. The extreme burden imposed on clinical facilities during the COVID-19 pandemic has provided a permissive environment for the emergence of clonal outbreaks of multiple Candida species, including C. auris and C. parapsilosis . Here we report the largest clonal CAC outbreak to date caused by fluconazole resistant (FLZR) and echinocandin tolerant (ECT) C. parapsilosis . Sixty C. parapsilosis strains were obtained from 57 patients at a tertiary care hospital in Brazil, 90% of them were FLZR and ECT. Although only 35.8% of FLZR isolates contained an ERG11 mutation, all of them contained the TAC1 L518F mutation and significantly overexpressed CDR1 . Introduction of TAC1 L518F into a susceptible background increased the MIC of fluconazole and voriconazole 8-fold and resulted in significant basal overexpression of CDR1 . Additionally, FLZR isolates exclusively harboured E1939G outside of Fks1 hotspot-2, which did not confer echinocandin resistance, but significantly increased ECT. Multilocus microsatellite typing showed that 51/60 (85%) of the FLZR isolates belonged to the same cluster, while the susceptible isolates each represented a distinct lineage. Finally, biofilm production in FLZR isolates was significantly lower than in susceptible counterparts Suggesting that it may not be an outbreak determinant. In summary, we show that TAC1 L518F and FKS1 E1393G confer FLZR and ECT, respectively, in CAC-associated C. parapsilosis . Our study underscores the importance of antifungal stewardship and effective infection control strategies to mitigate clonal C. parapsilosis outbreaks.